For Whom the Bell Tolls : Climate Change and Inequality - Cevik, Serhan; Jalles, Joao Tovar.. (Washington, D.C. : International Monetary Fund, 2022)
Climate change is the defining challenge of our time with complex and evolving dynamics. The effects of climate change on economic output and financial stability have received considerable attention, but there has been much less focus on the relationship between climate change and income inequality. In this paper, we provide new evidence on the association between climate change and income inequality, using a large panel of 158 countries during the period 1955-2019. We find that an increase in climate change vulnerability is positively associated with rising income inequality. More interestingly, splitting the sample into country groups reveals a considerable contrast in the impact of climate change on income inequality. While climate change vulnerability has no statistically significant effect on income distribution in advanced economies, the coefficient on climate change vulnerability is seven times greater and statistically highly significant in the case of developing countries due largely to weaker capacity for climate change adaptation and mitigation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Distribution; Foreign Exchange; Macroeconomic Policy, Macroeconomic Aspects of Public Finance, and General Outlook; Multiple or Simultaneous Equation Models; Multiple Variables